KARAKTERISTIK EMISI GAS BUANG INSINERATOR MEDIS DIRUMAH SAKIT JIWA DADI MAKASSAR SULAWESI SELATAN - Marosin, Riyanto (Jurnal Teknologi Lingkungan, 2004)
The disposal of hospital waste needs special treatment. To assist the hospital waste treatment of Makassar city, UPT-LSDE, BPPT has been designed and developed a medical incinerator with the capacity of 50 kg/jam at Rumah Sakit Jiwa Dadi Makassar in the year 2002.After one year operation, the system was provided by recuperator and tested to measure the emission characteristics into operation modes. The first mode, incinerator was run without operating recuperator and the second by operating recuperator. Characteristics of exhaust gas emissions were monitor continuously during test by using a poprtable gas analyzer, while particulate sampling was done as standard sampling Method 5 EPA.The test results show that pollution gas emissions, except CO, are under the regulation standard limits of Environmental Control Agency Head Decree No.Kep-03/BAPEDAL/09/1995. While particulate concentration in exhaustgas is under the standard limit of Environmental State Minister Decree No.13/1995. However, waste feeding and air combustion distributor of the tested incinerator need to be modified to achieve optimum combustion.This paper presents the exhaust gas characteristics of the tested unit that was performed on 19 September 2003.